Long term impacts of endozoochory and salinity on germination of wetland plants after entering simulated seed banks - Espinar, José L.; Figuerola, Jordi; Green, Andy J. (Frontiers in Plant Science, 2023)
Migratory waterbirds disperse a broad range of angiosperms by endozoochory (seed dispersal via gut passage), especially plants in coastal wetlands. However, there is no previous information about the capacity of seeds to remain in the seed bank after waterbird endozoochory, and very little about how wetland salinity can influence the effect of gut passage on germination. We collected seeds of Juncus subulatus (Juncaceae), Bolboschoenus maritimus, and Schoenoplectus litoralis (Cyperaceae) from Doñana marshes in Spain. All three species are considered to have physiological dormancy. After gut passage following ingestion by ducks, seeds were stored in darkness in solutions with six different conductivities (1, 2, 4, 8, 16, and 32 dSm-1), for periods of 1, 6, or 12 months to simulate presence in a seed bank. After storage, 1800 seeds of each plant species assigned to these treatments were subjected to germination tests in demineralized water, together with 1800 control seeds that had not been ingested before storage. All species germinated readily after storage, with or without gut passage beforehand. Storage time and salinity both had important effects on germinability and time to germination, which differed between control and ingested seeds, and between plant species. After ≥6 months, germinability of Cyperaceae was enhanced by gut passage (≤25% higher than control seeds) at some salinities. Only J. subulatus showed consistently lower germinability after passage (≤30%). Only B. maritimus showed consistently slower germination after passage (≤33%). Salinity effects were more complex after passage, but increasing salinity did not generally have a negative impact on germination of ingested seeds. When compared to additional seeds that had not been stored before germination tests, storage reduced germinability in J. subulatus (≤39% reduction), but increased it in B. maritimus (≤17%) and S. litoralis (≤46%). Seeds dispersed by waterbird endozoochory may be easily incorporated into wetland seed banks, where they can remain halotolerant and delay germination until conditions become suitable. This can benefit wetland plants by increasing rates of long-distance dispersal, gene flow, and establishment of new populations. Avian gut passage can have positive and species-specific effects on germination in plants with persistent seed banks and/or physiological dormancy.